Effect of process parameters on colour attributes of rice kheer produced using mechanized system - Singh, Mayank; Kumar, Bikram; Minz, P S; Singh, Gursharn (Indian Journal of Dairy Science, 2018)
Large scale production of kheer using in-line system is a rapid process as compared to conventional method. In-line system decreases the processing time due to which heat induced colour changes and browning was found to be reduced.Â This investigation studies the influence of process parameters viz., milk concentration and heat treatment on colour attributes of kheer. Initial milk concentration in scarped surface heat exchanger and conical process vat pressure were varied at different discrete levels i.e., 20, 22 and 24% TS and 147.1, 196.1, 245.1 kPa, respectively. Prediction equations were developed to determine various colourmetric attributes of kheer viz., CIE L*, a*, b* values, whiteness index, brownness index and colour difference (Î”E) on the basis of processing parameters. The data generated gives a range of parameters in which the product was not caramelized means no over cooking of product occurred during processing.